Upaya Kerjasama Meksiko dan Amerika Serikat dalam Mengatasi Kartel Narkoba di Meksiko sebagai Transnational Organized Crime - Idris, Muhammad; Togatorop, Benita L (Universitas Komputer Indonesia, 2023)
Organization of illegal drug trade that occurred in Mexico has reached the limit that endangers human security there. The reason is, Mexico is a source of fulfilling the needs of illegal narcotics by the United States which causes many cases of murder and violence that occur in Mexico and the United States. This is also very detrimental to the country, thus making Mexico and the United States decide to establish bilateral cooperation in an effort to resolve the problem of the spread of this drug. This research was made to find out what efforts and steps were taken by Mexico in eradicating drug cartels. This study uses a descriptive qualitative method, in which data is obtained from the results of literature studies through journals, books, websites and so on. The results obtained will explain how successful the efforts of bilateral cooperation between Mexico and the United States are to eradicate drug cartels. Keywords— Drugs, Drug Cartels, Mexico, United States